Exploring workplace mental health among Indian employees: A systematic literature review and future research agenda - Anu Sohal; Dipanker Sharma (Social Sciences and Humanities Open)
The Sustainable Development Goals (SDGs), specifically SDG-3 (Good Health and Well-being) and SDG-8 (Decent Work and Economic Growth) emphasize the overall mental well-being of employees in the workplace. This review aims to systematically understand what is already known about mental health in the workplace (MHW) among Indian employees through performance analysis (citations, journal, and corpus performance) and content analysis using the TCCM (theoretical perspectives, context, characteristics, and methods) approach. The present review used a SPAR-4-SLR (Scientific Procedures and Rationales for Systematic Literature Reviews) protocol to extract the 38 high-quality articles published between 2004 and 2024. Our findings revealed that stress, anxiety, and depression are the most common indicators of MHW, which are increasingly recognized as a global concern. The results of the content analysis highlighted the extensive use of the Conservation of Resources (COR) theory and the Job Demands-Resources (JD-R) model in the MHW research. This review identified various antecedents and outcomes of MHW, providing a conceptual framework for guiding future research. Further, this review offers valuable insights into future avenues and implications for improving mental health conditions and overall well-being.